Analisis Faktor-Faktor Yang Mempengaruhi Nasabah Memilih Hasanah Card Sebagai Kartu Kredit Study Kasus BSI KCP Krakatau - Fadhila Audi Ubay; Ahmad Perdana Indra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to analyze the factors that influence customers' decisions in choosing Hasanah Card as the credit card of choice. Credit cards, as an important financial instrument, increasingly dominate consumer choices in managing their finances. In this context, Hasanah Card stands out as an attractive option in the credit card market, especially in the sharia-based financial environment. This research uses an analytical approach to identify the main factors that shape customer preferences for the Hasanah Card. These factors involve aspects such as sharia compliance, benefits and incentives, comfort of use, and brand image. Through surveys and data analysis, this research aims to provide in-depth insight into what factors most influence customers' decisions in choosing a Hasanah Card credit card. The results of this research are expected to provide an important contribution to the understanding of the Islamic banking industry, especially in the context of credit cards. In addition, these findings are expected to provide guidance for financial service providers to improve the quality of their products, accommodate customer needs, and strengthen Hasanah Card's position in an increasingly competitive market.